A resettable supramolecular platform for constructing scalable encoders. Issue 55 (21st June 2019) - Yang, Chunrong; Yang, Shu; Song, Lingbo; Yao, Ye; Lin, Xiao; Cai, Kaicong; Yang, Qianfan; Tang, Yalin
Abstract : A supramolecular platform prototype for implementing resettable encoding functions was designed, which could be configured into a series of encoders, from 4-to-2 to 7-to-3, and even 14-to-4 ECs. Abstract : A supramolecular platform prototype for implementing resettable encoding functions was designed, which could be configured into a series of encoders, from 4-to-2 to 7-to-3, and even 14-to-4 ECs.